Bilateral Lower Lip Sinuses Associated with Bilateral Cleft Lip - Masood H. Khan; Arshad H. Khan (Indian Journal of Plastic Surgery, 1990)
A case of bilateral lower lip sinuses associated with bilateral cleft of the lip is being presented.